(untitled) (Al-Academy, 2026)
The organizations concerned with thought and learning seek to create Appropriate educational environments are created by using modern scientific methods and approaches. One of these methods is interactive design, which focuses on creating smooth and attractive interactive experiences for users. The research problem was defined as :What is it And Available ways to enhance the design Interactive in the used furniture in Educational institutions The research aims to enhance the design .In an interactive context to Educational furniture development An interactive model was identified, represented by the smart interactive table, from which three models were chosen as a research sample. After using a form for descriptive analysis of the models, a set of results and conclusions were reached, the most prominent of which were: share Appearance simplicity to Authority A Design Interactive At both levels of form YAnd functional in achieving a To interact Positive between producer and recipient. 2. Learning methods are developing significantly and rapidly using modern interactive technologies, which contribute to enhancing interactive design at the institutional level in general and at the individual level for users in particular.